Hability to Work, Workload and Communication to Employee Performance Perumda Drinking Water - Datus, Teos; Susanti, Febsri (Bina Bangsa International Journal of Business and Management, 2023)
This research is motivated by the performance of Perumda Water Drinking South Service Area that has not been implemented optimally, so that the services provided are not optimal for the community. This study aims to determine the effect of work ability, workload, and communication on the performance of the Padang Air Perumda Water Supply employees. The research population is all 45 employees of the Padang Air Perumda Water Company. The sampling technique used was total sampling. The number of samples that can be used for analysis purposes is 45 people. Testing the research hypotheses was carried out using the statistical analysis technique of multiple regression analysis. The results of the study found that: (1) work ability had a significant influence on the performance of the Padang Air Perumda Water Company employees, (2) the workload had a significant influence on the Padang Air Drinking Water Company employee performance, (3) Communication had a significant effect on performance of Padang Water Perumda employees. (4) Work ability, workload and communication together have a significant influence on the performance of the Padang Air Perumda Water Supply employees